Functional traits and phylogeny jointly regulate the effects of environmental filtering and dispersal limitation on species spatial distribution - Wang, Minghui; Liu, Wande; Chen, Zhaoquan; Li, Shuaifeng; Huang, Xiaobo; Hu, Zihan; Shang, Ruiguang (Frontiers in Forests and Global Change, 2024)
Studying the spatial distribution of species is crucial for elucidating the maintenance mechanisms of biodiversity and exploring the ecological processes underlying community stability and succession. In this study, we employed spatial point process modeling to identify and quantify the processes contributing to the spatial distribution of species. Simultaneously, we investigated the relationship between functional traits and the characteristics of species spatial distribution in conjunction with phylogenetic studies. The results revealed that the LGCP model effectively described all species, indicating that spatial patterns of species might be shaped by the combined influences of environmental filtering and dispersal limitation. Disparities in species spatial distribution were elucidated by characterizing functional traits, such as body size and resource conservation. Incorporating phylogenetic information enhanced the predictive capacity of functional traits in explaining species spatial distribution. This study underscores the significance of the joint effects of environmental filtering and dispersal limitation in generating species spatial distribution patterns. Integrating spatial point process models with considerations of functional traits and phylogeny proves to be an effective approach for comprehending the mechanisms governing species combinations.